NADPH Oxidase Inhibitor Apocynin Attenuates PCB153-Induced Thyroid Injury in Rats - Ablikim Abliz; Chen Chen; Wenhong Deng; Weixing Wang; Rongze Sun (International Journal of Endocrinology)
PCBs, widespread endocrine disruptors, cause the disturbance of thyroid hormone (TH) homeostasis in humans and animals. However, the exact mechanism of thyroid dysfunction caused by PCBs is still unknown. In order to clarify the hypotheses that NADPH oxidase (NOX) and subsequent NF-κB pathway may play roles in thyroid dysfunction, sixty Sprague-Dawley rats were randomly divided into four groups: control group, PCB153 treated (PCB) group, received apocynin with PCB153 treatment (APO + PCB) group, and drug control (APO) group. Serum thyroid hormone levels were evaluated. The morphological change of thyroid tissue was analyzed under the light and transmission electron microscopy. NOX2, 8-OHdG, and NF-κB expression in the thyroid tissue was evaluated by immune-histochemical staining. Oxidative stress and inflammatory cytokines were detected. The following results were reduced after apocynin treatment: (1) serum thyroid hormone, (2) thyroid pathological injuries, (3) thyroid MDA, (4) thyroid ultrastructural change, (5) serum inflammatory cytokines, and (6) thyroid expression of NOX2, 8-OHdG, and NF-κB. These results suggested that NOX inhibition attenuates thyroid dysfunction induced by PCB in rats, presumably because of its role in preventing ROS generation and inhibiting the activation of NF-κB pathway. Our findings may provide new therapeutic targets for PCBs induced thyroid dysfunction.